Paying Attention to Payoffs in Analogy-Based Learning - Topi Miettinen (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2009)
This paper introduces the payoff-confirming analogy-based expectation equilibrium (PCABEE) as a way to refine the set of analogy-based equilibria and the associated admissible analogy partitions. In addition to the actions of others, own payoff history provides information about others' strategies but, yet, non-Bayesian Nash equilibria may exist both with an incorrect and a correct prior. We provide general conditions when this happens. Two stylized employer-employee interactions, one with a correct and one with an incorrect prior, are provided illustrating how PCABEE can be used to analyze robust stereotypes and how incorrect such stereotypes may lead to discrimination.
Keywords: C72; D82; 330; analogy expectations; bounded rationality; curse; learning; discrimination; stereotypes